The Effect Of Halal Labels On Purchasing Decision Of Halal Cosmetic Products With Interest As Intervening Variable - Najmudin, Najmudin; Ridwan, Iwan; Jakaria, Jakaria; Maisaroh, Ima; Sujanah, Nanah (Universitas Siliwangi, 2023)
Introduction to The Problem: Most of Indonesia's population is Muslim, the number reaches 86.9% or 237.53 million people, among their needs, especially Muslim women, is cosmetics, the data shows that there is a very high gap between the number of halal cosmetic products and non-halal cosmetics circulating in the market, so not a few Muslim women who purchase non-halal cosmetics. Purpose/Objective Study: This study aims to determine (1) the effect of halal labels on purchasing decisions for halal cosmetic products (2) the influence of halal labels on interest in buying halal cosmetic products (3) the influence of buying interest on purchasing decisions for halal cosmetic products, and (4) the influence of halal labels on a decision to purchase halal cosmetic products through the mediation of buying interest. Design/Methodology/Approach: The method used in this research is descriptive quantitative, with a population of all students of the modern Islamic boarding school Assa'adah, Serang Regency, users of halal cosmetics, sampling technique using purposive sampling, and data collection techniques using questionnaires. The data was processed using Smart PLS 3.2.9 software and analyzed using the method of structural equation modeling (SEM) with partial least squares (PLS) approach. Findings: The results of this study indicate that(1) Halal labels have a positive effect on purchasing decisions for halal cosmetic products (2) Halal labels have a positive effect on interest in buying halal cosmetic products (3) Purchase intentions have a positive effect on purchasing decisions for halal cosmetic products, and (4) Halal labels have a positive effect on decisions purchase of halal cosmetic products through the mediation of buying interest.Paper Type: Research Article